2013
DOI: 10.1152/ajpregu.00574.2012
|View full text |Cite
|
Sign up to set email alerts
|

The effect of low-to-moderate-dose ethanol consumption on rat mammary gland structure and function and early postnatal growth of offspring

Abstract: High levels of alcohol consumption during pregnancy can lead to growth deficits in early postnatal life. However, the effects of low-to-moderate alcohol consumption during pregnancy are less clearly defined. The aim of this study was to determine whether low-to-moderate ethanol (EtOH) consumption throughout pregnancy in the rat alters maternal mammary gland morphology and milk protein levels, thereby affecting lactation and the growth of pups after birth. Sprague-Dawley rats were fed an ad libitum liquid diet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 54 publications
(55 reference statements)
0
5
0
Order By: Relevance
“…Sub-optimal blood pressure levels should be minimised to prevent hypotensive symptoms, particularly in the elderly who are vulnerable to falls [44]. On the other hand, the hypotensive phenotype in female ethanol-exposed offspring may buffer other hallmarks of disease previously reported in these offspring including altered glucose handling [22], and left ventricular hypertrophy and fibrosis [20] and thus could be construed as cardioprotective.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sub-optimal blood pressure levels should be minimised to prevent hypotensive symptoms, particularly in the elderly who are vulnerable to falls [44]. On the other hand, the hypotensive phenotype in female ethanol-exposed offspring may buffer other hallmarks of disease previously reported in these offspring including altered glucose handling [22], and left ventricular hypertrophy and fibrosis [20] and thus could be construed as cardioprotective.…”
Section: Discussionmentioning
confidence: 99%
“…At 30 min, the BAC averaged ~ 0.03% and by 5 h was undetectable in most animals. This model of maternal EtOH exposure does not affect maternal nutrition or pregnancy outcomes, such as litter size or birth weight [22], and the level of alcohol exposure is equivalent to approximately two standard drinks within an hour in humans. We hypothesised that chronic low prenatal EtOH exposure would alter blood pressure profiles, endothelial vasodilator function and arterial stiffness in the offspring at 12 months of age, equivalent to middle age in humans.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, elevated fasted plasma glucose and elevated insulin (Akison et al, 2019;Harper, Tunc-Ozcan, Graf, & Redei, 2014) occur in PAE rat offspring in adulthood. However, other preclinical studies did not observe that PAE affects glucose and insulin concentration (Amos-Kroohs, Nelson, Hacker, Yen, & Smith, 2018;Elton, Pennington, Lynch, Carver, & Pennington, 2002;Probyn et al, 2013). The fetal insulin hypothesis postulates that both birth weight and T2DM are two phenotypes of the same genotype (Shields, Freathy, & Hattersley, 2010).…”
Section: Pae and Metabolic Programmingmentioning
confidence: 95%
“…Primarily, these models have shown that alcohol decreases nephron endowment and consequently increases blood pressure in the offspring following binge . Our lowmoderate model (6% EtOH v/v) showed that prenatal alcohol at these levels altered protein composition in the breast milk without affecting the mammary gland (Probyn et al, 2013b). Additionally, offspring exposed to a low-moderate dose of alcohol prenatally developed pulmonary fibrosis over time (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) Hence similar to our other alcohol models, the findings from this thesis should be seen as a part of a much larger picture.…”
Section: Long-term Consequences Of Periconceptional Alcohol Exposure mentioning
confidence: 89%
“…Primarily, these models have shown that alcohol decreases nephron endowment and consequently increases blood pressure in the offspring following binge . Our lowmoderate model (6% EtOH v/v) showed that prenatal alcohol at these levels altered protein composition in the breast milk without affecting the mammary gland (Probyn et al, 2013b). Additionally, offspring exposed to a low-moderate dose of alcohol prenatally developed pulmonary fibrosis over time (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) months old males), which would compromise respiratory lung capacity (Probyn et al, 2013a); exhibited left ventricular hypertrophy and fibrosis associated with decreased maximal aortic flow velocity (8 months) (Nguyen et al, 2014); and induced anxiety-like behaviour via structural changes in the basolateral amygdala (8 and 15 months) (Cullen et al, 2013).…”
Section: Long-term Consequences Of Periconceptional Alcohol Exposure mentioning
confidence: 89%